Spatial Changes in Labour Market Inequality - Joanne Lindley; Stephen Machin (Institute for the Study of Labor (IZA), 2013)
We study spatial changes in labour market inequality for US states and MSAs using Census and American Community Survey data between 1980 and 2010. We report evidence of significant spatial variations in education employment shares and in the college wage premium for US states and MSAs, and show that the pattern of shifts through time has resulted in increased spatial inequality. Because relative supply of college versus high school educated workers has risen faster at the spatial level in places with higher initial supply levels, we also report a strong persistence and increased inequality of spatial relative demand. Bigger relative demand increases are observed in more technologically advanced states that have experienced faster increases in R&D and computer usage, and in states where union decline has been fastest. Finally, we show the increased concentration of more educated workers into particular spatial locations and rising spatial wage inequality are important features of labour market polarization, as they have resulted in faster employment growth in high skill occupations, but also in a higher demand for low wage workers in low skill occupations. Overall, our spatial analysis complements research findings from labour economics on wage inequality trends and from urban economics on agglomeration effects connected to education and technology.
Keywords: J31; R11; 330; college wage premium; education shares; spatial changes; relative demand; polarization